Mudanças nos conceitos de ansiedade nos séculos XIX e XX : da Angstneurose ao DSM-IV - Viana, Milena de Barros (2010)
Anxiety has been a well-studied subject for centuries. Nevertheless, as a circumscribed pathology, anxiety only appears in medical reports at the end of the 19th century, with the works of Sigmund Freud. From clinical observations, Freud detached Angstneurose ( anxiety neurosis ) from neurasthenia, also separating chronic anxiety from anxiety attacks. Although psychoanalytic classifications of anxiety were well-accepted until the mid 1900 s, in the following decades different factors contributed to re-orientate Psychiatry, particularly towards Biology. One important factor was the development of Psychopharmacology. With the so-called psychopharmacological revolution , which began in the 1960 s, the modern descriptive and operational - classifications of mental disorders appeared. The DSM-III (Diagnostic Statistical Manual of Mental Disorders, in its third version), published in 1980, inaugurates a new relationship between Psychiatry and Psychopathology, although its conception of mental disorder is not a very clear one. The birth of panic disorder as a nosological category is particularly related to this change in perspective, since it takes place from the pharmacological observation of the therapeutic effects of a new drug, imipramine. In this sense, the purpose of the present study is to investigate the concepts of anxiety adopted in Psychiatry, particularly from the second half of the 19th century until the development of the DSM-IV. At first, the present study will focus on the development of Angstneurose as a clinical entity, by Freud. For that, a brief examination of the clinical terms adopted to designate anxiety states before Freud s time will be performed. Also, the transformations of the Freudian ideas concerning anxiety will be discussed, from a conceptual and diagnostic stand point. In a second moment, the historical evolution of what the diagnostic manuals for mental disorders call anxiety disorders will be investigated, emphasizing the reorganization that these new classification systems bring to the understanding of the concept of anxiety. An attempt to establish a parallel between these new nosological entities and the Freudian categories will be performed. At last, possible points of intersection between Psychiatry and Psychoanalysis, which might contribute to a better understanding of mental phenomena, will be discussed, on the basis of Freud s incursions into Biology.